2022
DOI: 10.4081/ija.2022.2044
|View full text |Cite
|
Sign up to set email alerts
|

Soil refinement accelerates in-field degradation rates of soil-biodegradable mulch films

Abstract: Soil-biodegradable mulch films are a promising solution to replace conventional polyethylene-based mulch films, the use of which has led to negative environmental impacts. Soil-biodegradable mulch films are specifically designed to be incorporated into the soil at the end of the cropping cycle, and are expected to be biodegraded by soil microorganisms. The biodegradability of such products must be tested under laboratory-controlled conditions following international standards, although these can fail to repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…In any case, area loss may be a better indirect indicator of biodegradation than mass loss, as the latter showed questionable results, in some cases appearing to increase over time (Figure 2F). Indeed, other studies have reported that area loss is a more reliable indicator than mass loss (e.g., Bianchini et al, 2022).…”
Section: Interaction Between Crop Residues and Mulch Filmmentioning
confidence: 99%
See 3 more Smart Citations
“…In any case, area loss may be a better indirect indicator of biodegradation than mass loss, as the latter showed questionable results, in some cases appearing to increase over time (Figure 2F). Indeed, other studies have reported that area loss is a more reliable indicator than mass loss (e.g., Bianchini et al, 2022).…”
Section: Interaction Between Crop Residues and Mulch Filmmentioning
confidence: 99%
“…Examples include studies that have investigated the degradation of soil-biodegradable mulch films into macro and then microplastics followed by a quantification via chemical extraction (Li et al, 2023). Some other studies have placed mulch film samples in mesh bags, which allow the adhesion of soil to the film, ensuring the passage of water and microorganisms (Bianchini et al, 2022;Sintim et al, 2020;Tsuboi et al, 2022). In these studies, film area or mass loss, measured with infrared spectroscopy or nuclear magnetic resonance, was used to estimate degradation.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, pNP-C4 hydrolytic activity can aid in the detection of the microbial activity associated with the biodegradation of polyester-based biodegradable mulch films in cultivated field soils. Bianchini et al (2022) conducted open-field experiments where they evaluated the effects of soil refinement on the degradation rates of three different commercial soil-biodegradable mulch films after their incorporation into the soil. Their results show that soil refinement significantly accelerated the degradation of the tested films.…”
mentioning
confidence: 99%